2015
DOI: 10.1016/j.biomaterials.2014.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Implications of protein corona on physico-chemical and biological properties of magnetic nanoparticles

Abstract: Interaction of serum proteins and nanoparticles leads to a nanoparticle-protein complex formation that defines the rational strategy for a clinically relevant formulation for drug delivery, hyperthermia, and magnetic resonance imaging (MRI) applications in cancer nanomedicine. Given this perspective, we have examined the pattern of human serum protein corona formation with our recently engineered magnetic nanoparticles (MNPs). The alteration in particle size, zeta potential, hemotoxicity, cellular uptake/cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(123 citation statements)
references
References 51 publications
9
114
0
Order By: Relevance
“…Due to the discrepancy in the published results, the relationship between protein adsorption on NP and the decrease of the cellular internalization of NP remains to be established. Indeed, some studies show that protein adsorption on NP decreases their cellular uptake while other tend to demonstrate the opposite [18,19,25,[29][30][31][32]. Furthermore, it is difficult to draw firm conclusions from results dealing with different NP types, different functionalization groups, different cellular models, different biological assays, etc.…”
Section: Introductionmentioning
confidence: 89%
“…Due to the discrepancy in the published results, the relationship between protein adsorption on NP and the decrease of the cellular internalization of NP remains to be established. Indeed, some studies show that protein adsorption on NP decreases their cellular uptake while other tend to demonstrate the opposite [18,19,25,[29][30][31][32]. Furthermore, it is difficult to draw firm conclusions from results dealing with different NP types, different functionalization groups, different cellular models, different biological assays, etc.…”
Section: Introductionmentioning
confidence: 89%
“…It could be considered as the major proteins on the magnetic NP at 50% serum concentration. 36 In contrast, phagocytosis of NPs by dendritic cells was identical in various concentrations of protein mixtures. This result could be explained by particle uptake by phagocytes, possibly not dependent on the total binding protein quantity but the abundance of recognizable proteins on the particle surface.…”
Section: Protein Concentrationsmentioning
confidence: 96%
“…4,42 In addition, physiological milieus influence the interaction of biological systems with NPs and can determine the fate and biosafety of NPs. 7 Thus, comprehensive characterization of the NPs in physiological conditions is a fundamental step prior to assessing the in vivo toxicity of Cu NPs. The hydrodynamic diameter and zeta potential of Cu NPs indicated that Cu NPs have a tendency to aggregate/agglomerate in vehicle (pH 6.5) and simulated intestinal (pH 7.8) conditions.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Furthermore, the physiological milieu influences the interaction between biological systems and NPs and can determine the fate and biosafety of NPs. 7 Currently, with the widespread use of NPs, health risks and environmental effects related to NP exposure have become of great concern. 8 In addition, the applications of NPs have been limited by lack of verification of biosafety.…”
Section: Introductionmentioning
confidence: 99%